KONFLIK GENDER NOVEL NAMAKU HIROKO KARYA NH. DINI - Jayanti, Heni Dwi; Nasution, Ismail; Helda, Trisna (Pendidikan Bahasa Indonesia, 2013)
This research is motivated by gender conflict and the problematict of the life of a woman named Hiroko who comes from a poor family who is always bullied and harassed when pitted fate of her dignity as a housemaid in the city. The focus of this research in the form of the question is